Hospital acquired acute renal failure - Kumar, Pankaj; Dogra, Varun Deep; Kapoor, Dhiraj; Kumar, Rupinder; Aggarwal, Vishnu Kumar; Kumar, Manoj; Shoeb, Ansari Mohd (International Journal of Research in Medical Sciences, 2017)
Background: Acute renal failure has continued to attract interest and stimulate investigators .This is in part, a reflection of many clinical entities that can result in an acute renal failure. HAARF is an important cause of morbidity and mortality and is associated with the ten fold increase in the risk of death during the hospitalization.14 Despite advances in diagnosis and management it still carries a high mortality. HAARF is associated with grave consequences. Some of the clinical setting leading to HAARF can be limited by monitoring of renal function, better control of infection, avoiding nephrotoxic drugs and initiation of therapy at the earliest. Present study is proposed to evaluate the incidence, etiological factors and measures to reduce the incidence of HAARF. Methods:All patients were admitted to RPGMC from Dec. 2010 to APRIL 2014. They were screened for the development of the ARF during their hospital stay. The parameters of Prakash et al. were taken for the diagnosis of HAARF. Results:In our present study HAARF was diagnosed in 88 patients of 56904 admission during 40 month period, representing 0.15% of the admission. Predisposing factors were present in 64 % of the patients. They were elderly age >60 years (22.72%), DM (13.64%), pre-existing renal disease (13.64%) and HTN (4.54%). It was due to nephrotoxic dugs in 45.45%, decreased renal perfusion in 22.72%, infections in 13.64%, hepatorenal syndrome 9.09% surgery in 4.54% and Weil’s disease in 4.54 %. Among the nephrotoxic drugs antibiotics were the most common and NSAIDs were the second most common etiological factors. Decrease renal perfusion secondary to volume depletion and heart failure were equally responsible for HAARF in 9.09% each. Septicemia was responsible for 4.54% of cases. Oliguric renal failure was seen in the 31.82% where as nonoliguric renal failure was seen in 50% of cases. Great majority of non oliguric renal failure was due to nephrotoxic drugs. Oliguric patients have longer duration of hospital stay and high mortality as compared to the non oliguric renal failure. A high s. creatinine and high urea levels at the time of admission were associated with the earlier development of HAARF. Oliguria and anuric patients had a longer duration of hospital stay. Overall mortality of HAARF was 18.18% and nephrotoxic drugs responsible for one half of the total mortality. Conclusion:High risk group patients for HAARF needs meticulous monitoring during hospital stay. Hospitalized patients on nephrotoxic drugs should have frequent renal function tests. Proper fluid and electrolyte balance in hospitalized patients needs special emphasis to avoid HAARF.